Multi-scale contrast enhancement of oriented features in 2D images using directional morphology. (January 2017) - Das, Debashis; Mukhopadhyay, Susanta; Praveen, S.R. Sai
Abstract: This paper presents a multi-scale contrast enhancement scheme for improving the visual quality of directional features present in 2D gray scale images. Directional morphological filters are employed to locate and extract the scale-specific image features with different orientations which are subsequently stored in a set of feature images. The final enhanced image is constructed by weighted combination of these feature images with the original image. While construction, the feature images corresponding to progressively smaller scales are made to have higher proportion of contribution through the use of progressively larger weights. The proposed method has been formulated, implemented and executed on a set of real 2D gray scale images with oriented features. The experimental results visually establish the efficacy of the method. The proposed method has been compared with other similar methods both on subjective and objective basis and the overall performance is found to be satisfactory. Highlights: This paper presents a contrast enhancement scheme for improving the visual quality of 2D gray scale image. This multi-scale method employs directional morphology which makes it specially suitable for images with directional features. The method has produced good results. The method does not enhance noise while improving the contrast of the 2D gray-scale images.